Experimental studies of the base flow from the nozzles with sudden expansion with micro jets - Chaudhary, Zakir Ilahi; Shinde, V.B; Bashir, Musavir; Khan, Sher Afghan (NOVA Science Publishers, 2016)
A method for evaluating the performance of micro jets, in a flow behind a highly expanded nozzle is presented. In the process, the pressure distribution of the flow behind the nozzle outlet is calculated for a defined range of Mach numbers. The outcome shows the existence of oblique shock, Mach waves, and expansion fan in the investigation depending upon the expansion level of the shear layer at the nozzle lip. The height of the backward facing step is 2.5. The range of NPRs chosen for this case is within 3 and 11.Since very small jets are used as active control method, four jets of one millimeter hole diameter are installed for flow control. It is observed that the control effectiveness is quite good for the entire range of L/D at around Mach 2.0. For L/D ranging from 10 to 2, the decrements in the suction at the base exhibits thirty per cent increase in base pressure with micro jets. The final argument is that efficacy of the flow regulation is case sensitive and to arrive at the optimum flow variable lot of runs are needed to draw the conclusions. Also, the efficacy of very small jets is improved for suitable pressure gradient. For over expanded jets the dynamic effectiveness is minimum. The nature of flow in the abruptly expanded duct, in the presence and absence of the flow manipulator is unaltered and hence, remains identical for most of the cases.